2013
DOI: 10.47657/201314769
|View full text |Cite
|
Sign up to set email alerts
|

The Reading Preferences of Primary School Children in Lahore

Abstract: The scope of this study aims at investigating reading preferences of children of Lahore city, which is the capital of Punjab province-Pakistan. It was assumed that proper attention towards providing reading opportunities to primary school students (First -Fifth grade) in Pakistan is vital while inculcating reading habits at that tender age. The study was conducted on 300 primary school students. A target group of 300 primary school students was selected for this study. Mainly survey method based on administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Static fiction is also among the reasons why a book is least preferred. Awais and Ameen (2013) and Clark and Foster (2005) stated that preschool children mostly prefer stories with adventurous plots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Static fiction is also among the reasons why a book is least preferred. Awais and Ameen (2013) and Clark and Foster (2005) stated that preschool children mostly prefer stories with adventurous plots.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adults should know children's book preferences, and they must bring them together with books prepared in line with their interests. However, through a literature review conducted for this current study, no previous research that dealt specifically with preschool children's book preferences was identified in Turkey, and generally, there are not enough studies on this subject (Awais & Ameen, 2013;Robinson, Larsen, Haupt & Mohlman, 1997). It is seen that the studies about children's book preferences are generally carried out with primary school children or with older age groups (Altunkaynak, 2018;Ateş, Çetinkaya & Yıldırım., 2012;Boraks, Hoffman ve Bauer, 1997;Brookshire, Scharff ve Moses, 2002;Harris, 2008;Chapman, Filipenko, McTavish & Shapiro, 2007;Repaskey, Schumm ve Johnson, 2017;Ulusoy, 2016;Wang, 2017;Yıldız, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Students' reading habits in a digital age have recently become a hot topic in academia. Children, adults, men, and women have all been studied to see how they vary from one another in their reading habits in Pakistan (Awais & Ameen, 2013;Ahmed, 1964). There was, however, no local published literature on the "reading tendencies of young" (as stated by this research) in a digital context.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain and Munshi (2011) studied the reading preferences of secondary school children of Bahawalpur. Awais and Ameen (2013) studied the reading preferences of primary school children (Generation Z) in the Lahore District. However, these studies too do not focus on the impact of electronic reading format on Generation Z's reading habits.…”
Section: Introductionmentioning
confidence: 99%